Analisis Pengaruh Ketinggian Tanah dan Kedalaman Sumur terhadap Suhu dan pH Air Sumur di Kabupaten Blitar - Muhammad Syafa Tirtana Sanjaya; Tamara Pingki (Jurnal Teori dan Aplikasi Fisika, 2022)
Abstract. The fulfillment of human daily needs cannot be separated from water. The water most used by the community is ground water. One of the factors that can affect water quality is the depth of the water source. The purpose of this study was to analyze the effect of soil height and well depth on the temperature and pH of well water in Blitar Regency. The data was taken from 4 sub-districts in Blitar Regency, namely Ponggok, Nglegok Kesamben, and Selorejo. The characteristics of the pH of the water have an average of 6.7 and a water temperature of 23.43?C. If the depth of the well is increased by 1 meter, the pH of the water will increase by 0.1177 units. If the depth of the well is increased by 1 meter, the water temperature will increase by 0.126?C. Based on the results of the simultaneous test, it is known that the depth of the well and the height of the soil have a significant effect on water pH and water temperature. Based on the results of the partial test, it is known that the depth of the well has no significant effect on water pH and water temperature. However, the height of the soil has a significant effect on water pH and water temperature. Based on the results of the model goodness test, it can be seen that the proportion of water pH variability can be explained by the variable depth of the well and the height of the soil by 36.03% and the remaining 63.97% is influenced by other variables outside the model and the proportion of water temperature variability can be explained by the variable depth of the well and the ground height is 92.58% and the remaining 7.42% is influenced by other variables outside the model.Keywords: Depth, Altitude, pH, Temperature.Abstrak. Pemenuhan kebutuhan sehari-hari manusia tidak dapat terlepas dari air. Air yang paling banyak dimanfaatkan masyarakat adalah air tanah. Faktor yang dapat mempengaruhi kualitas air salah satunya adalah kedalaman sumber air. Tujuan dari penelitian ini adalah menganalisis pengaruh ketinggian tanah dan kedalaman sumur terhadap suhu dan pH air sumur di Kabupaten Blitar. Data yang diambil berasal dari 4 kecamatan di Kabupaten Blitar, yaitu Ponggok, Nglegok Kesamben, dan Selorejo. Karaktersitik pH air memiliki rata-rata sebesar 6,7 dan suhu air sebesar 23,43?C. Jika kedalaman sumur bertambah 1 meter maka pH air akan bertambah sebesar 0,1177 satuan. Jika kedalaman sumur bertambah 1 meter maka suhu air akan bertambah sebesar 0,126?C. Berdasarkan hasil uji serentak diketahui bahwa kedalaman sumur dan ketinggian tanah berpengaruh signifikan terhadap pH air dan suhu air. Berdasarkan hasil uji parsial diketahui bahwa kedalaman sumur tidak berpengaruh signifikan terhadap pH air dan suhu air. Namun ketinggian tanah berpengaruh signifikan terhadap pH air dan suhu air. Berdasarkan hasil uji kebaikan model dapat diketahui bahwa proporsi variabelitas pH air dapat dijelaskan oleh variabel kedalaman sumur dan ketinggian tanah sebesar 36,03% dan sisanya sebesar 63,97% dipengaruhi variabel lain diluar model serta proporsi variabelitas suhu air dapat dijelaskan oleh variabel kedalaman sumur dan ketinggian tanah sebesar 92,58% dan sisanya sebesar 7,42% dipengaruhi variabel lain diluar model.Kata kunci: Kedalaman, Ketinggian, pH, Suhu.